2010
DOI: 10.1002/dvdy.22383
|View full text |Cite
|
Sign up to set email alerts
|

Neuron‐specific expression of atp6v0c2 in zebrafish CNS

Abstract: *Vacuolar ATPase (V-ATPase) is a multi-subunit enzyme that plays an important role in the acidification of a variety of intracellular compartments. ATP6V0C is subunit c of the V 0 domain that forms the proteolipid pore of the enzyme. In the present study, we investigated the neuron-specific expression of atp6v0c2, a novel isoform of the V-ATPase c-subunit, during the development of the zebrafish CNS. Zebrafish atp6v0c2 was isolated from a genome-wide analysis of the zebrafish mib ta52b mutant designed to ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…have the same number of V0-c V-ATPase subunits as in zebrafish (not shown). It was reported that the duplicated gene V0-cb is preferentially expressed in the zebrafish brain, being more specific at the presynaptic vesicles and is regulated by Notch signaling [27]. According to our RT-PCR data V0-ca has a ubiquitous expression (Figure 3B).…”
Section: Resultssupporting
confidence: 61%
See 2 more Smart Citations
“…have the same number of V0-c V-ATPase subunits as in zebrafish (not shown). It was reported that the duplicated gene V0-cb is preferentially expressed in the zebrafish brain, being more specific at the presynaptic vesicles and is regulated by Notch signaling [27]. According to our RT-PCR data V0-ca has a ubiquitous expression (Figure 3B).…”
Section: Resultssupporting
confidence: 61%
“…V-ATPases are also important during development in invertebrates [19,20] and vertebrates [21]. Its function is required for specific processes like acquiring left-right asymmetry [22,23], biliary function [24], bone formation [25,26] and neural system development [27,28]. The vacuolar ATPase complex from vertebrates is composed of at least 15 subunits arranged in two functional domains: V1 with subunits A, B, C, D, E, F, G and H and V0 with subunits a, c, c”/b and e. Both domains have a combined molecular weight around 750 kDa.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is present in endosomes, lysosomes, clathrin-coated vesicles and the Golgi complex, where it is essential to acidification and maintenance of endocytic and exocytic pathways [17]. Experiments in zebrafish embryos suggest a neuron-specific expression of the zebrafish ortholog atp6v0c2 where it is associated with presynaptic vesicles and involved in neurotransmitter storage [18]. PDPK1 (also known as PDK1) is a highly conserved protein kinase that is involved in many different signalling pathways (reviewed in [19]).…”
Section: Discussionmentioning
confidence: 99%
“…As a component of V0 domain of V-ATPase, ATP6V0C forms the proteolipid c-ring of the V-ATPase and plays a pivotal role in synaptic vesicle proton gradient generation and regulation of intra and extracellular pH value (Higashida et al, 2017;Xu et al, 2019). Experiments in zebrafish ortholog revealed that ATP6V0C2 is associated with neurotransmitter storage/secretion and involved in the control of neuronal excitability (Chung et al, 2010). Homozygous ATP6V0C knockout mice exhibit neonatal lethality, abnormal embryonic tissue morphology, and failure of zygotic cell division.…”
Section: Introductionmentioning
confidence: 99%